2022
DOI: 10.1172/jci161454
|View full text |Cite
|
Sign up to set email alerts
|

KRAS mutations as essential promoters of lymphangiogenesis via extracellular vesicles in pancreatic cancer

Abstract: Kirsten rat sarcoma virus ( KRAS ) gene mutations are present in more than 90% of pancreatic ductal adenocarcinomas (PDACs). KRAS G12D is the most frequent alteration, promoting preneoplastic lesions and associating with a more aggressive phenotype. These tumors possess increased intratumoral lymphatic networks and frequent lymph node (LN) metastases. In this issue of the JCI , Luo, Li, et al. explored the relationship between the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Lymphangiogenesis is directly related to LNM in various types of cancer, and exosomes and non-coding RNA have been proven to be involved in the process [ 30 33 ]. The IHC analysis using anti-podoplanin antibody indicated that the density of lymph vessels was much higher in patients with LNM (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Lymphangiogenesis is directly related to LNM in various types of cancer, and exosomes and non-coding RNA have been proven to be involved in the process [ 30 33 ]. The IHC analysis using anti-podoplanin antibody indicated that the density of lymph vessels was much higher in patients with LNM (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…KRAS has been identified as the most frequently mutated gene in human cancers that is responsible for 30% of all human carcinomas [1][2][3][4]. Studies found that the mutant version of KRAS was presented in 90% of pancreatic cancers [5][6][7], and up to 40% of colorectal cancers [3]. RAS interacts with proteins involved in many cellular processes, including cell growth, differentiation, mitosis, and metabolism.…”
Section: Introductionmentioning
confidence: 99%